International Resources Guide to Hazardous Chemicals - Manufacturers, Agencies, Organizations, and Useful Sources of Information - Greene, S.A. (William Andrew Publishing/Noyes, 2011)
This book is intended for chemists, toxicologists, laboratory technicians, manufacturers, safety professionals and government personnel involved in environmental and industrial safety and health matters.